2019
DOI: 10.1021/acs.jafc.9b02208
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Degradation of N-ε-Carboxymethyllysine, a Major Glycation End-Product, by Human Intestinal Bacteria

Abstract: Modifications of lysine contribute to the amount of dietary advanced glycation end-products reaching the colon. However, little is known about the ability of intestinal bacteria to metabolize dietary N-ε-carboxymethyllysine (CML). Successive transfers of fecal microbiota in growth media containing CML were used to identify and isolate species able to metabolize CML under anaerobic conditions. From our study, only donors exposed to processed foods degraded CML, and anaerobic bacteria enrichments from two of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 35 publications
(81 reference statements)
0
63
0
Order By: Relevance
“…Most of the diet-derived AGEs escape digestion and absorption and pass through the gastrointestinal tract to the colon ( 12 , 13 ). Here, they are available as substrates for gut microbial metabolism ( 14 , 15 ). However, the extent to which long-term intake of processed food impacts intestinal permeability and influences the outcome of microvascular disorders such as CKD is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the diet-derived AGEs escape digestion and absorption and pass through the gastrointestinal tract to the colon ( 12 , 13 ). Here, they are available as substrates for gut microbial metabolism ( 14 , 15 ). However, the extent to which long-term intake of processed food impacts intestinal permeability and influences the outcome of microvascular disorders such as CKD is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Various approaches have focused on studying the intestinal microbiota either by quantitative techniques of microorganism culture [9] or by quantifying 16s rRNA fragment as a marker-gene. Marker-gene techniques include denaturing gradient gel electrophoresis (DGGE) [19], terminal restriction fragment length polymorphism (T-RFLP) [20], quantitative PCR (qPCR) [21], fluorescence in situ hybridization (FISH) [22] or plasmid-clone capillary Sanger sequencing [23]. However, for complex and diverse ecosystems such as intestinal microbiota, the previously mentioned methods have provided incomplete profiles of microbial community structure.…”
Section: Introductionmentioning
confidence: 99%
“…Recent growing evidence suggested that the human gut microbiome can metabolize dAGEs, possibly as much as 40% for ingested CML [ 38 ]. CML has been shown to be metabolized by the microbiome into several sub-products, including biogenic amines and fatty acids, notably N-carboxymethylcadaverine, N-carboxymethylaminopentanoic acid, N-carboxymethyl-Δ1-piperideinium ion, and 2-amino-6-(formylmethylamino)hexanoic acid [ 39 , 40 ]. Less is known about the specific actions of these catabolic products within the colorectum, or the possible downstream molecules that can be produced from them.…”
Section: Discussionmentioning
confidence: 99%